Part I: Pd(II)-catalyzed ring-expansion of cyclic 2-azidoalcohols for synthesis of azaheterocycles. Part II: Cu(II)-catalyzed aerobic oxidation of benzyl cyanides for synthesis of carboxylic acids - Xu, Yanjun (2012)
This thesis described two catalytic reactions: (1) Pd(II)-catalyzed ring-expansion of cyclic 2-azidoalcohols for synthesis of azaheterocycles; (2) Cu(II)-catalyzed aerobic oxidation of benzyl cyanides for synthesis of carboxylic acids.